✔ 最佳答案
令n為>0的正整數,試證:,9^n-4^n-6^n+1為30的倍數
Sol
先證明9^n-4^n-6^n+1為5的倍數
當n=1時
9^1-4^1-6^1+1
=0
=0*5
So
n=1時為真
設n=k時為真即存在整數p,使得
9^k-4^k-6^k+1=5p
9^k=5p+4^k+6^k-1
9^(k+1)-4^(k+1)-6^(k+1)+1
=9*(5p+4^k+6^k-1)-4*4^k-6*6^k+1
=45p+5*4^k+3*6^k-8
3*6^k-8=3*(5+1)^k-8
存在整數m,使得
3*6^k-8=3*(5m+1)-8=15m-5
So
9^(k+1)-4^(k+1)-6^(k+1)+1
=45p+5*4^k+15m-5
=5(9p+4^k+3m-1)
So
n=k+1時為真
再證明9^n-4^n-6^n+1為6的倍數
當n=1時
9^1-4^1-6^1+1
=0
=0*6
So
n=1時為真
設n=k時為真即存在整數p,使得
9^k-4^k-6^k+1=6p
9^k=6p+4^k+6^k-1
9^(k+1)-4^(k+1)-6^(k+1)+1
=9*(6p+4^k+6^k-1)-4*4^k-6*6^k+1
=54p+5*4^k+3*6^k-8
5*4^k-8=5*(3+1)^k-8
存在整數m,使得
5*4^k-8=5*(3m+1)-8=15m-5
So
5*4^k-8為3的倍數
So
存在整數s,使得
5*4^k-8=6s
9^(k+1)-4^(k+1)-6^(k+1)+1
=54p+3*6^k+5*4^k-8
=54p+3*6^k+6s
So
n=k+1時為真
9^n-4^n-6^n+1為5的倍數,9^n-4^n-6^n+1為6的倍數
So
9^n-4^n-6^n+1為30的倍數